Event-Studies with a Continuous Treatment - Callaway, Brantly,Goodman-Bacon, Andrew,Sant'Anna, Pedro H. C. (National Bureau of Economic Research, 2024)
This paper considers methods for defining aggregate parameters of interest in a difference-in-differences design with a continuous and staggered treatment. It also discusses how aggregation choices often simplify estimation
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Ereignisstudie; Differenz von Differenzen; Ökonometrie; Econometrics; Semiparametric and Nonparametric Methods: General